2012
DOI: 10.1016/j.ncl.2012.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia

Abstract: Insomnia is a common disorder, with individual and societal consequences. Advances have been made in the understanding of insomnia and its treatment options. However, cognitive behavioral therapy and Food and Drug Administration-approved pharmacologic therapies have limitations, the former primarily involving access and the latter involving potential side effects. Further research is needed to optimize management strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…Sleep problems are ubiquitous . Difficulty falling and staying asleep can be seen in persons with and without comorbid medical and psychiatric disorders, and it has been estimated that about a third of people have at least one insomnia symptom .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep problems are ubiquitous . Difficulty falling and staying asleep can be seen in persons with and without comorbid medical and psychiatric disorders, and it has been estimated that about a third of people have at least one insomnia symptom .…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological approaches to the treatment of insomnia have included GABA‐A receptor agonists (for example, the benzodiazepine temazepam and the non‐benzodiazepine zolpidem), melatonin receptor agonists (for example, ramelteon), and histamine H 1 receptor antagonists (for example, doxepin) .…”
Section: Introductionmentioning
confidence: 99%
“…These individuals are rarely studied in clinical drug trials, and the development of new therapeutics to target occasional difficulties with sleep maintenance may be worthwhile given the tolerability and safety concerns associated with some prescription and OTC sleep products. 24,25 Low-dose gabapentin (250 mg) is being investigated as a potential therapy for occasional disturbed sleep and has been evaluated in this self-identified population. In a randomized, controlled clinical trial, single doses of gabapentin 250 and 500 mg were shown to significantly improve measures of sleep maintenance compared with placebo, using a 5-h phase advance model to induce transient insomnia in individuals with occasional disturbed sleep.…”
mentioning
confidence: 99%
“…In recent years, advances have been made in the understanding of insomnia and its treatment options [19]. However, the breakdown of disciplinary boundaries makes it more difficult for scientists or clinicians to reconcile all of the publications relevant to their research [6].…”
Section: Discussionmentioning
confidence: 99%
“…Although pharmacological and cognitive behavioral therapies have become mainstream in insomnia therapy, side effects of hypnotics and difficulty in accessing CBT-I still limit their use in clinical practice, and alternative therapies for insomnia still have a role in the general population [19]. Furthermore, aside from self-help strategies such as reading or relaxation, our literature search shows that the most frequently studied alternative treatments are herbal medicine and acupuncture.…”
Section: Discussionmentioning
confidence: 99%